Clinical Phenotype and Inheritance in Patients With C9ORF72 Hexanucleotide Repeat Expansion: Results From a Large French Cohort - Esselin, Florence; Mouzat, Kevin; Polge, Anne; Juntas-Morales, Raul; Pageot, Nicolas; De la Cruz, Elisa; Bernard, Emilien; Lagrange, Emmeline; Danel, Véronique; Alphandery, Sébastien; Labar, Laura; Nogué, Erika; et al. (Frontiers in Neuroscience, 2020)
Background: In familial amyotrophic lateral sclerosis ALS cases the presence of an abnormal C9ORF72 repeat expansion (C9RE) is the most frequent genetic cause identified. Various clinical phenotypes have been described in relation to the presence of C9RE, including psychiatric disorders or Huntington-like symptoms. In a subset of sporadic ALS, C9RE have also been described. In the present study all index-cases with ALS and C9RE identified in our centre and their clinical profile were described as well as neurological and psychiatric characteristics of identified family members. Clinical characteristics of ALS patients were compared to 999 patients with sporadic ALS (SALS) from our database. Results: From the 70 index-cases with ALS identified, a total of 200 individuals were studied, 118 with ALS, 32 with FTD, 37 with ALS/FTD and 13 with psychiatric disorders. A familial history was present in 57 of index-cases (81%). In ALS and ALS/FTD cases with C9RE age of onset (AoO) was earlier than in SALS cases, p<0.0001 and p=0.008, respectively. Apparently sporadic cases with ALS (n=13) had an earlier AoO compared to familial ALS ones, p<0.0001. Within families, there was an earlier AoO and an earlier age at death in index-cases and their siblings compared to their parental generation (p<0.01). There was also a significant intrafamilial correlation for bulbar onset of ALS. The parental generation had significant female predominance compared to index-cases and their siblings (sex ratio 0.47 vs. 1.4, p=0.004). In the group with psychiatric disorders, suicide was prominent (n=9) and mean age was 54 yrs. Conclusions: This study showed an earlier AoO in ALS cases both in familial and apparently sporadic cases, an intrafamilial correlation for bulbar onset, a predominant female transmission and a high frequency of suicides in relatives. Earlier AoO in index-cases and their siblings compared to the parental generation is in favor of an anticipation. The predominance of female transmission, suggests a role of gender either on transmission of the genetic trait or on the size variation of the C9RE, or both. Intrafamilial correlation suggests that genetic aspects underlie the occurrence of bulbar onset in ALS patients.